1889 Minn. Gen. Stat. 1006 - (:unkn) unknown (My University, 1888)
Making, Selling, etc., Dangerous Weapons, §§ 333-34: Prohibited manufacturing, selling, giving, or disposing of a slungshot, sandclub, or metal knuckles, or selling or giving a pistol or firearm to a minor without magistrate consent. Also prohibited carrying a concealed slungshot, sandclub, or metal knuckles, or a dagger, dirk, knife, pistol or other fire-arm, or any dangerous weapon.
Keywords: CARRY - CONCEALED; TRANSFER - MINORS; TRANSFER, MANUFACTURE & POSSESSION